The Effectiveness Of Dynamic Stretching And Nordic Hamstring Exercises To Increase Hamstring Muscle Flexibility In FIA UB Futsal Club Players - Ahmad Naufal Alifa; Bayu Prastowo; Irawan, Dimas Sondang (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2024)
Hamstring injury is one of most often injury in futsal. Hamstring muscle flexibility is the ability of the muscles in the lower extremities to stretch optimally. Weakness in the hamstring muscles can cause shortening and impaired flexibility which occurs in every human being, so exercises are needed that stretch the shortened muscle tissue and restore flexibility to the hamstring muscles. This research aims to determine the effectiveness of providing dynamic stretching and nordic hamstring and to increase hamstring muscle flexibility in FIA UB futsal club players. The research method used is a type of quasi-experimental research with a two group pre and post test method. The research was conducted at FIA UB on 24 FIA UB fusal players using purposive sampling technique. The sit and reach test was employed as the measurement tool in this study. The analysis used univariate and bivariate using the independent t-test comparison test. The research results show that there is a p value (0.000). The statistical test results show that the results are less than 0.05, indicating that H1 is accepted and H0 is rejected. In conclusion, it can be stated that there is a comparison between before and after being given nordic hamstring intervention training which is more effective than dynamic stretching for increasing hamstring muscle flexibility in FIA UB futsal players.